2006
DOI: 10.1021/jm060126s
|View full text |Cite
|
Sign up to set email alerts
|

Acyclic Nucleoside Analogues as Inhibitors ofPlasmodiumfalciparumdUTPase

Abstract: We report the discovery of novel uracil-based acyclic compounds as inhibitors of deoxyuridine 5'-triphosphate nucleotidohydrolase (dUTPase), an enzyme involved in nucleotide metabolism that has been identified as a promising target for the development of antimalarial drugs. Compounds were assayed against both P.falciparum dUTPase and intact parasites. A good correlation was observed between enzyme inhibition and cellular assays. Acyclic uracil derivatives were identified that showed greater or similar potency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
61
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 19 publications
0
61
0
Order By: Relevance
“…Having completed the diphenyl linker chain, attachment of the uracil was carried out with Mitsunobu methodology. The use of polymer-supported triphenylphosphine, a procedure previously used in our laboratories, [9] ensured a cleaner reaction without the triphenylphosphine oxide by-product, which is sometimes difficult to remove. To ensure monoalkylation at the N1 position of uracil, N3-protected uracil was used.…”
Section: Three-c Analoguementioning
confidence: 99%
See 4 more Smart Citations
“…Having completed the diphenyl linker chain, attachment of the uracil was carried out with Mitsunobu methodology. The use of polymer-supported triphenylphosphine, a procedure previously used in our laboratories, [9] ensured a cleaner reaction without the triphenylphosphine oxide by-product, which is sometimes difficult to remove. To ensure monoalkylation at the N1 position of uracil, N3-protected uracil was used.…”
Section: Three-c Analoguementioning
confidence: 99%
“…However, following Mitsunobu coupling and benzoyl deprotection, a low yield of alcohol intermediate 10 was obtained. It was found that coupling of ethyl 4-bromobutanoate to N3 benzoyl-protected uracil 7 [9] could be achieved cleanly in good yield after heating in N,N-dimethylformamide for 1 h. Reduction of the ester using a sodium borohydride/methanol system reported by Da Costa et al [11] led to simultaneous reduction and benzoyl deprotection to give 10.…”
Section: Four-c Analoguesmentioning
confidence: 99%
See 3 more Smart Citations